The role of communication skills in the promotion of productivity of health human resource in Iran: A cross-sectional study - Behrooz Pouragha; Mahnaz Keshtkar; Mahdieh Abdolahi; Hojjat Sheikhbardsiri (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Organization survival is dependent on communications and managers spend a main portion of their time to establish communications. The identification, improvement, and development of communication skills serve as the essential components of successful organizations. The present study aimed to investigate the role of communication skills in human resource (HR) productivity in North Iran and aimed to investigate the role of communication skills in health HR (HHR) productivity in North Iran. METHODS: The study employed a cross-sectional design and was conducted in six deputies supervised by the Alborz University of Medical Sciences, in 2019. The statistical population included all 302 employees were selected as the sample population according to the Cochran's formula. Using two researcher-made questionnaires of communication skills and HHR productivity, we assessed the role of communication skills in HHR productivity. RESULTS: According to the research findings, there were significant relationships between communication skills including verbal skills, listening skills, and effectiveness skills with HHR productivity (P ≤ 0.05). There was a significant relationship between age group, gender, level of education, and travel home-university distance with communication skills and resource productivity of employees (P ≤ 0.05). CONCLUSION: This study examines the role of communication skills in the promotion of HHR productivity who work in the administrative section of the University of Medical Sciences in Iran. Findings suggest that health planners and authorities may need to examine factors that contribute to the promotion of the communication skills for increase HHR productivity of employees and improved performance of health organizations.